Metabolic engineering of Clostridium autoethanogenum - Liew, Fung Min (2016)
Gas fermentation has emerged as a promising technology that converts waste gases containing CO, CO2 and H2 (also known as syngas) into fuels and chemical commodities. Employed by LanzaTech Inc., Clostridium autoethanogenum is an industrial acetogen that converts gases into ethanol, 2,3-butanediol, acetate, and lactate. Metabolic engineering offers unique opportunities to eliminate side-products, synthesize novel, high-value molecules as diversification strategies, and increase productivities of natural products. However, there had been no scientific reports of genetic manipulation of this acetogen so the overall goal of this PhD project was to develop genetic tools for this gas-utilizing microorganism and construct a hyper-ethanol producing strain via metabolic engineering. The formulation of electroporation and conjugation procedures allowed exogenous DNA to be routinely introduced into the bacterial host. ClosTron mutagenesis and Allele-Coupled Exchange (ACE) techniques were fully exemplified in this bacterium during the construction of knockout, in-frame deletion, and overexpression mutants. Carbon monoxide dehydrogenases (cooS1, cooS2 and acsA) were specifically targeted to elucidate their roles in supporting CO oxidation and carbon fixation. In the ethanol formation pathway, inactivation of bi-functional aldehyde/alcohol dehydrogenases (adhE1 and adhE2) impaired growth on pure CO but elevated ethanol titres. Conversely, inactivation of the more highly expressed aldehyde:ferredoxin oxidoreductase (aor1), but not the weakly expressed aor2, significantly reduced ethanol production, highlighting the importance of aor1 in autotrophic ethanol formation. A double KO mutant of aor1 and aor2 was also generated via ClosTron mutagenesis and pyrE-mediated allelic exchange. In an effort to engineer a robust biocatalyst, the native chaperone systems groESL and/or grpE-dnaK-dnaJ were overexpressed in C. autoethanogenum, resulting in enhanced tolerance towards ethanol, heat and salts. In summary, this study demonstrated the genetic tractability of C. autoethanogenum and revealed gene targets for future metabolic engineering of a hyper-ethanol producing acetogen.